On the spin-liquid phase of one-dimensional spin-1 bosons - Essler, F; Shlyapnikov, G; Tsvelik, A (Institute of Physics Publishing, 2009)
We consider a model of one-dimensional spin-1 bosons with repulsive density-density interactions and antiferromagnetic exchange. We show that the low energy effective field theory is given by a spin-charge separated theory of a Tomonaga-Luttinger Hamiltonian and the O(3) non-linear sigma model describing collective charge and spin excitations respectively. At a particular ratio of the density-density to spin-spin interaction the model is integrable, and we use the exact solutions to provide an independent derivation of the low energy effective theory. The system is in a superfluid phase made of singlet pairs of bosons, and we calculate the long-distance asymptotics of certain correlation functions. © 2009 2009 IOP Publishing Ltd and SISSA.